On the evolutionary edge of altruism: A game-theoretic proof of Hamilton's rule for a simple case of siblings - Oded Stark; You Qiang Wang (Institute for Advanced Studies (IHS), 2003)
We offer a game-theoretic proof of Hamilton's rule for the spread of altruism. For a simple case of siblings, we show that the rule can be derived as the outcome of a one-shot prisoner's dilemma game between siblings.
Keywords: A13; C70; D64; 330; evolution of altruism; Hamilton's rule; one-shot prisoner's dilemma game; Altruismus; Gefangenendilemma; Theorie; Evolutionäre Spieltheorie